Renewable Therapy Potential of Allogeneic Bone Marrow-Derived Mesenchymal Stem Cells for Idiopathic Pulmonary Fibrosis - Bawono, Aloysius Krishartadi Damar; Balqis, Gasela Zalianti; Haq, Rais Amaral; Sari, Ratna Dewi Puspita; Utama, Winda Trijayanthi; Daulay, Suryani Agustina (SAFE-Network, 2024)
Idiopathic pulmonary fibrosis (IPF) is a rare chronic respiratory disease characterized by progressive fibrotic changes in lung tissue of unknown origin, resulting in severe decline in lung function and poor prognosis with a median survival of 3 to 5 years. Current pharmacological therapies, including nintedanib and pirfenidone, aim to slow disease progression but are limited by side effects and lack of efficacy in reversing established fibrosis. This literature review explores emerging therapeutic approaches for IPF using data from PubMed, Google Scholar, and ScienceDirect databases. The review highlights mesenchymal stem cell (MSC) therapy, specifically allogeneic bone marrow-derived MSCs, as a promising option. MSC therapy demonstrates superior efficacy in improving forced vital capacity (FVC) by 3.7%, surpassing the effects of nintedanib (3.3%) and pirfenidone (-4.8%), while exhibiting minimal adverse effects. The findings underscore the potential of MSC therapy as a renewable treatment option for IPF, suggesting a paradigm shift towards addressing both disease progression and lung function restoration in affected individuals.